Emergency management of ludwig’s angina: a case report - Nur H. Alimin; Endang Syamsuddin (Journal of Dentomaxillofacial Science, 2017)
Objective: Ludwig’s angina is a severe diffuse cellulitis in mandibular region that commonly caused by odontogenic infection. Due to its acute on onset, spread rapidly, involving the submandibular, sublingual region bilaterally and submental region, this condition consider as an emergency because it can cause airway obstruction.Methods: A 40 years old male patient came to Dr. Hasan Sadikin hospital emergency room with pain and swelling at lower jaw, drooling, hard to breath and limitation in opening his mouth. He was diagnosed with sepsis and Ludwig’s angina. Tracheostomy was performed to secure the airway, continued with teeth extraction, incision and drainage to eliminate the source of infection. Combination of intravenous antimicrobial was administered.Results: An advanced case of Ludwig’s angina and its management was reported. The patient showed a good response to the treatment and the condition was improved.Conclusion: Ludwig’s angina is a rare emergency condition which potentially life-threatening. Patient showed a significant recovery due to immediate and rapid management in securing airway patency and infection source control to prevent the spread of infection and further complications.